The impact of union dissolution on moving distances and destinations in the UK - Peteke Feijten; Maarten van Ham (Institute for the Study of Labor (IZA), 2011)
The number of people who have ever experienced a divorce, or a split up of a non-marital union, is rising every year. It is well known that union dissolution has a disruptive effect on the housing careers of those involved, often leading to downward moves on the housing ladder. Much less is known about the geographies of residential mobility after union dissolution. There are reasons to expect that those who experienced a union dissolution are less likely to move over longer distances, which could negatively influence the spatial flexibility of the labour force. This study contributes to the existing literature by investigating the occurrences of moves, distances moved and the destinations of moves after union dissolution. The paper also contributes to the literature by not only investigating the effect of divorce, but also splitting up, and repartnering on mobility. Using longitudinal data from the British Household Panel Survey (BHPS) and logistic regression models we found that union dissolution has a significant effect on the occurrence of moves and moving distances.
urn:nbn:de:101:1-201104134313
Keywords: J12; J61; R21; R23; 330; union dissolution; splitting up; divorce; housing career; spatial mobility; longitudinal data; BHPS; United Kingdom; Scheidung; Wohnstandort; Entfernung; Großbritannien